2019
DOI: 10.1097/ana.0000000000000580
|View full text |Cite
|
Sign up to set email alerts
|

International Multicenter Survey of Perioperative Management of External Ventricular Drains: Results of the EVD Aware Study

Abstract: The Content Outline for Initial Certi cation in Anesthesiology re ects the subject matter within the specialty of anesthesiology and provides the framework for the assessment of knowledge. It is the basis for the written examinations (BASIC, ADVANCED, Part 1, and In-Training) of the core specialty. The Content Outline will serve as a resource in the preparation for the written components of initial board certi cation as board-certi ed anesthesiologists are expected to have knowledge within each of the topics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Yet, it appears that anesthesiologists are often neither trained in managing external ventricular drains nor aware of standard guidelines for their management. 57 Careful management of external ventricular drain is essential to ensure adequate management of the ICP and the CPP, preventing over-or under-drainage of CSF and to prevent infective complications. The Society for Neuroscience in Anesthesiology and Critical Care has published guidelines for the perioperative management of patients with external ventricular drains and lumbar drains.…”
Section: Rapid Restoration Of Cerebral Perfusionmentioning
confidence: 99%
“…Yet, it appears that anesthesiologists are often neither trained in managing external ventricular drains nor aware of standard guidelines for their management. 57 Careful management of external ventricular drain is essential to ensure adequate management of the ICP and the CPP, preventing over-or under-drainage of CSF and to prevent infective complications. The Society for Neuroscience in Anesthesiology and Critical Care has published guidelines for the perioperative management of patients with external ventricular drains and lumbar drains.…”
Section: Rapid Restoration Of Cerebral Perfusionmentioning
confidence: 99%
“…We found significant variation between centers in the following 4 areas: (1) ability to identify a normal ICP waveform, (2) factors associated with elevated ICP when transporting patients with the EVD clamped, (3) the possibility of draining CSF and accurately measuring ICP at the same time, and (4) the elements to be considered during transport to/from the intensive care unit. Based on the EVD aware3 and the EVD PoP8 studies, there is heterogeneity among hospital EVD policies. The heterogeneities related to intrahospital transport may be evident in the responses to these questions in the module.…”
Section: Discussionmentioning
confidence: 99%
“…1 The Society for Neuroscience in Anesthesiology and Critical Care (SNACC) has published evidence-based guidelines for the perioperative management of EVDs, highlighting indications, potential complications, intraoperative management, and recommendations for continued medical education. 2 However, the EVD aware study 3 found that > 50% of anesthesiologists are uncomfortable managing patients with an EVD in situ and that 90% have not received any formal training in EVD management.…”
mentioning
confidence: 99%
“…An anesthesiologist may provide perioperative care to 0 to ≥100 patients annually with CSF diversion devices and those undergoing diversion procedures 5 . While not all anesthesiologists may be comfortable managing CSF diversion devices, 5 a basic understanding of the relevant pathophysiology and nuances of different devices and procedures is essential. An anesthesiologist may be involved in cases where the neurosurgeon places an EVD, or the patient may already have an indwelling EVD.…”
Section: What Is the Relevance Of Csf Diversion Devices And Procedure...mentioning
confidence: 99%